Evaluation of Different Modelling Methods Used for Erosion Prediction - Mohyaldinn, Mysara Eissa (2011)
In this paper, the three methods of modeling erosion in pipe components due to sand production with oil and gas are investigated by the mean of comparison of results obtained from Salama model, DIM model, and DPM model, the three models selected to represent empirical, semi-empirical, and CFD methods, respectively. The DPM model was assumed as a benchmark based on which Salama model and DIM model were investigated. The results obtained from the DIM model agree fairly with those obtained from the DPM model whereas Salama model highly overestimates the DPM model. Based on the comparison, Salama model was modified to increase its accuracy, from one hand, and to extend it to application to oil, from the other hand